Enhancing Community Self-Sufficiency: A Case Study of Motorcycle Maintenance Training in North Balikpapan - Suardi, Suardi; Pawara, Muhammad Uswah; Mahmuddin, Faisal; Klara, Syerly (Indonesian Journal of Maritime Technology, 2024)
Motorcycle maintenance and service training represents a strategic initiative to enhance technical skills and empower individuals to independently maintain the condition of their vehicles. This training program was implemented in RT 33 Balikpapan with the primary objective of imparting both practical and theoretical knowledge on motorcycle maintenance and repair to local residents. The training methodologies employed encompassed classroom-based theoretical sessions, live demonstrations, and hands-on practical work under the guidance of experienced instructors. The outcomes of this training program indicated a substantial improvement in participants' comprehension and technical proficiency. Prior to the training, most participants possessed minimal knowledge regarding the fundamental aspects of motorcycle maintenance. However, post-training assessments revealed that participants were capable of performing various routine maintenance tasks such as oil changes, brake inspections, and chain adjustments. Furthermore, participants demonstrated the ability to diagnose and repair common issues, including carburetor contamination and ignition system malfunctions. The success of the program was evaluated not only by the enhancement of technical skills but also by the increased confidence and self-reliance of the participants in maintaining their motorcycles. The broader implications of this training include cost savings on vehicle maintenance for residents, improved driving safety, and potential economic uplift through the establishment of independent motorcycle service ventures. In conclusion, the motorcycle maintenance and service training program conducted in RT 33 Balikpapan had a marked positive impact, enhancing the technical capabilities of the community and fostering community empowerment through the development of practical skills.